Сучасні аспекти формування загальної стратегії аудиту - Москаль, Н. В. (Видавництво Львівської політехніки, 2014)
Досліджено порядок формування загальної стратегії аудиту у контексті розвитку теорії аудиту, наявності різноманітних підходів до його планування та спрямування практики аудиторської діяльності до постійного удосконалення організації та методики його проведення. До передумов розроблення загальної стратегії аудиту віднесено ознайомлення для отримання розуміння суб’єкта господарювання і його середовища, діагностику безперервності діяльності, оцінку ризику та суттєвості, визначення умов аудиту. На основі розглянутих елементів та передумов формування загальної стратегії аудиту запропоновано застосовувати на рівні окремих суб’єктів аудиторської діяльності типову структуру загальної стратегії аудиту, яка би забезпечувала належну якість його подальшого планування та здійснення. Ключові слова: планування аудиту, загальна стратегія аудиту, оцінка ризику та суттєвості, умови аудиту, об’єкти аудиту, аудиторські процедури. Audit planning is a vital area of the audit primarily conducted at the beginning of audit process to ensure that appropriate attention is devoted to important areas, potential problems are promptly identified, work is completed expeditiously and is properly coordinated. Audit planning means developing a general strategy and a detailed approach for the expected nature, timing and extent of the audit. The auditor plans to perform the audit in an efficient and timely manner. The auditor should develop and document a general strategy describing the expected scope and conduct of the audit. In developing the overall audit strategy we suggest to include: knowledge of the business; general economic factors and industry conditions affecting the entity's business; important characteristics of the entity, its business, its financial performance and its reporting requirements including changes since the date of the prior audit; understanding the Accounting and Internal Control Systems; the accounting policies adopted by the entity and changes in those policies; the expected assessments of inherent and control risks and the identification of significant audit areas; the setting of materiality levels for audit purposes; the identification of complex accounting areas including those involving accounting estimates; possible change of emphasis on specific audit areas; coordination, direction, supervision and review; other matters. It is advisable to use the typical structure of the overall audit strategy for individual audit firms. This will improve the process of forming the overall audit strategy and ensure proper quality of future planning and auditing. Key words: audit planning, the general audit strategy, risk assessment and evaluation of materiality, conditions of audit, objects of auditing, the audit procedures.
Modern aspects of the general audit strategy
Keywords: планування аудиту; загальна стратегія аудиту; оцінка ризику та суттєвості; умови аудиту; об’єкти аудиту; аудиторські процедури; audit planning; the general audit strategy; risk assessment and evaluation of materiality; conditions of audit; objects of auditing; the audit procedures